BELT AND ROAD INITIATIVE: OVERVIEW, OBJECTIVES AND IMPLICATIONS - A. A. Kireeva (Сравнительная политика)
The article aims to analyze the PRC’s Silk Road Economic Belt and 21st Century Maritime Silk Road, called the Belt and Road Initiative (BRI). It provides initiative assessment: overview, conceptualization, institutionalization and key priorities. Three interconnected groups of objectives define BRI: China’s economic development goals, trade, investment policy and foreign policy. The BRI is set to provide stimulus to China’s development with new external and internal sources of economic growth amid ongoing China’s economic transformation, deal with structural problems, foster high-quality production and transition to innovative development model while upgrading its involvement into regional and global value chains. Chinapositions BRI as a new mega-project of regional integration with Chinaas its leader, capable of providing public goods. It aims to create alternative energy and transport routes, improve relations with neighboring countries, alleviate concerns over China’s rise in politics, security and economics and form positive sentiments in its neighborhood. The BRI has become a key dimension of China’s economic and foreign policy with a strategic goal to consolidate China’s periphery with economic means in the first place. The BRI has the potential to provide enormous stimulus to the development and integration of Asia and Eurasia, simultaneously determining the prospects of China’s becoming a dominant power in East Asia and Eurasia and realizing the ‘Chinese dream’.